2021
DOI: 10.3390/pr9101796
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Gum Hydrocolloid Polyelectrolyte Complexes (PEC) for Biomedical Applications: Their Properties and Drug Delivery Studies

Abstract: The utilization of natural gum polysaccharides as the vehicle for drug delivery systems and other biomedical applications has increased in recent decades. Their biocompatibility, biodegradability, and price are much cheaper than other materials. It is also renewable and available in massive amounts, which are the main reasons for its use in pharmaceutical applications. Gum can be easily functionalized with other natural polymers to enhance their applications. Various aspects of the utilization of natural gums … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…In general, it was observed that spray-dried nostoc is in the nanoparticulate range, with values ranging from 0.9 to 648.7 nm, which would allow better molecular interaction by acting as a hydrocolloid with other substances [ 2 , 3 , 7 , 26 , 28 , 68 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, it was observed that spray-dried nostoc is in the nanoparticulate range, with values ranging from 0.9 to 648.7 nm, which would allow better molecular interaction by acting as a hydrocolloid with other substances [ 2 , 3 , 7 , 26 , 28 , 68 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the CH hydrocolloid, it was observed that 95.8% reported a mean size of 421.7 nm, this size would allow the improvement of the electrostatic and chemical interactions during the adsorption process of heavy metals and the formation of colloids and suspension due to its ζ potential (−27.14 mV) ( Table 3 ) [ 18 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the CH hydrocolloid, it was observed that 95.8% reported a mean size of 421.7 nm, this size would allow the improvement of the electrostatic and chemical interactions during the adsorption process of heavy metals and the formation of colloids and suspension due to its ζ potential (−27.14 mV) (Table 3) [18,[45][46][47][48]. The ζ potential allows knowing the solution stability of powdered materials, the absolute value between 21 to 40 mV indicates medium stability, and <20 mV allows easy agglomeration and sedimentation [49][50][51].…”
Section: Particle Size ζ Potential and Sem Images Of The Clay And Hyd...mentioning
confidence: 99%
“…The properties of the product depend strongly on the ratio of cationic and anionic groups; and in the case of non-stoichiometric systems, the product is water soluble. Other important factors affecting the characteristics of the resulting product are pH and the mixing sequence of the particular components [ 48 , 49 ]. The scheme depicting the formation of polyelectrolyte complex is presented in Figure 4 .…”
Section: Micro- and Nanoparticle Fabrication Methodsmentioning
confidence: 99%